Training on making patterned cloth with the shibori technique to improve the skills of the inmates of the Sukamiskin Kelas IIa Bandung women's prison - Tessa Eka Darmayanti (Community Empowerment, 2022)
Improving skills through workshops on making shibori patterned fabrics held at the Sukamiskin Women's Penitentiary in the Arcamanik, Bandung City is a community service activity. This activity aims to create a “creativity space” that helps prison inmates gain additional skills and confidence which can later be used as provisions when they return to their families and communities. The method of implementing the service begins by introducing several tools and several techniques for making motifs that can be created through various shibori techniques. Furthermore, providing various ideas to be able to develop their application into various forms of decorative and aesthetic ready-to-use products. The manufacture of these ready-to-use products will later be included in the activity program at the class II women's prison. From the results of the service activities, they were able to produce a creative space through the practice of making shibori motifs from plain white cloth into fabrics with various beautiful colorful motifs.